Effect of antenatal corticosteroids on neonatal outcome in term elective caesarean section: a randomised controlled trial - Panwar, Megha; Agrawal, Shailja; Pachauri, Deepti; Anand, H. P.; Kamble, Bhushan Dattatray; Gurbani, Ruchi (International Journal of Research in Medical Sciences, 2022)
Background: Infants born at term by elective caesarean section are more likely to develop respiratory morbidity than infants born vaginally. Prophylactic corticosteroids in singleton preterm pregnancies accelerate lung maturation and reduce the incidence of respiratory complications. Thus, the aim of this randomized controlled trial was to assess the effect of antenatal corticosteroids on neonatal outcome among term pregnant women undergoing elective caesarean section. Methods: It was an open labelled randomized controlled trial conducted among women with term pregnancy of 37-38+6 weeks and planned for caesarean section at term and who were willing to participate in the study. We randomized 50 pregnant women into intervention group which received antenatal corticosteroids in the form of injection dexamethasone 12 mg IM, 4 doses at 12 hourly intervals before term elective caesarean section and 50 pregnant women into control group which did not receive antenatal corticosteroid. Fetal outcomes were compared in both groups after caesarean section. Data were analysed using SPSS vs.20. Results: Nearly half (54%) of pregnant women belonged age group of 21-25 years and majority (58%) of pregnant women belonged to 38-39 weeks of gestation. Out of 50 pregnant women in intervention group, only two percent neonates developed RDS, four percent neonates developed transient tachypnea of neonate (TTN) and six percent neonates required NICU admission which was lower than control group. However, difference between fetal outcomes in intervention and control group was not statistically significant (p>0.05). Conclusions: Administration of prophylactic antenatal corticosteroids before 48 hours of elective term caesarean section does not have impact on fetal outcome in our study.